Leaky-wave wires antenna for future D- Band 6G communication systems - Sohoo, Arslan A.; Ahmed, Izhar; Seman, Fauziahanim Che; Ishak, Nurul Syafeeqa; Khee, Yee S. (2023)
Future communication generation such as 6G and beyond will be utilizing the terahertz band, as this range promises potential benefits such as a high data rate. However, designing different electronic components for 6G is complicated and has low fabrication precision due to its small wavelength. Additionally, the cost is also very high as compared to 5G components. These antennas feature high data rates, small size, and high bandwidth and are a critical component for the communication system. Therefore, in this study, an antenna design is proposed for the future sub-THz communication system that operates at D- band which is proposed for the 6G communication system. The simulation analysis shows that the proposed antenna has a high gain of 9.9 dBi at 120 GHz operating frequency and good performance characteristics for the complete D-band. The design of the proposed antenna is simple, low-cost, and does not require any complex fabrication, and can be the potential leaky-wave antenna for future 6G if properly excited.